'These people are vulnerable, they aren't criminals': Mental health, the use of force and deaths after police contact in England. (March 2020) - Baker, David; Pillinger, Claire
This paper considers deaths after police contact 1 in England of people experiencing mental health issues. It uses rich qualitative data from interviews with the families of nine people who died after police contact to examine how they died. The paper aims to assess the police role in providing a de facto service for people undergoing mental health crises and how the use of force might affect the outcomes of such encounters. The paper aims to examine the manifest tensions when an enforcement agency is tasked with providing a duty of care to vulnerable people in society. Key findings are that force is disproportionately more likely to be used on people with mental health issues, and also disproportionately more likely to be used on people from Black and Minority Ethnic communities. Further findings provide insight on the use of mechanical restraint and the way in which inappropriate transportation can exacerbate the effects of restraint.